2019
DOI: 10.1016/j.ancene.2019.100197
|View full text |Cite
|
Sign up to set email alerts
|

Glacio-archaeological evidence of permanent settlements within a glacier end moraine complex during 980-1840 AD: The Miyar Basin, Lahaul Himalaya, India

Abstract: This study presents glacio-archaeological evidence from the Miyar basin, Lahaul Himalaya, that points towards the former presence of a well settled agricultural society, within a glacier end moraine complex. Three high altitude villages (Tharang, Phundang and Patam, now in ruins) with elaborate irrigation networks thrived within the end moraine complex of Tharang glacier at 3700 m a.s.l. Evidence exists in the form of dilapidated houses which had an organised internal space, chronologically constrained by radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
(99 reference statements)
2
9
0
Order By: Relevance
“…LIA, Little Ice Age; pOcS, prior year October to current year September. that the settlement abandonment occurred during late-eighteenth and early-nineteenth centuries due to reduced temperature and increased snowfall (Saini et al, 2019). The study of Qiao and Yi (2017) also found a significant role of precipitation in controlling the pattern of glaciation during the LIA over the Himalaya.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…LIA, Little Ice Age; pOcS, prior year October to current year September. that the settlement abandonment occurred during late-eighteenth and early-nineteenth centuries due to reduced temperature and increased snowfall (Saini et al, 2019). The study of Qiao and Yi (2017) also found a significant role of precipitation in controlling the pattern of glaciation during the LIA over the Himalaya.…”
Section: Discussionmentioning
confidence: 80%
“…Saini et al. (2019) also marked the three sites of Tharang, Phundang and Patam (presently abandoned) showing settled agriculture coincident with warm temperature and limited snowfall. During 1300–1600 CE, there was no glacial expansion in the region and the period was generally warmer compared to the present day, which allowed permanent settlements within the end‐moraine complex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The situation is worst during winters when heavy snowfall in the IHR cut-off many areas from the rest of the country. The temperature in the Himalayan region is typically cold (average maximum of 20°C and minimum −15°C) and offers sub-zero temperature conditions (Saini et al, 2019). These freezing conditions pose a technical challenge for efficient composting and sometimes may even lead to the failure of the composting process in the cold hilly regions (Hou et al, 2017).…”
Section: Challenges Of Solid Waste Management In the Indian Himalayanmentioning
confidence: 99%
“…It has been reported that IHR states like Jammu and Kashmir have made use of only 0.06% of total biogas plants installed in the country (Lohan et al, 2015). The foremost reason behind such a low number is the cold ambient temperature in IHR (Saini et al, 2019). The temperature plays a significant role in biogas production; hence, the cold temperature in IHR acts as a limiting factor in carrying out sufficient AD process (Lohan et al, 2015).…”
Section: Anaerobic Digestionmentioning
confidence: 99%